2021
DOI: 10.1038/s41598-021-92611-3
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of MeV electrons into the mesosphere accompanying pulsating aurorae

Abstract: Pulsating aurorae (PsA) are caused by the intermittent precipitations of magnetospheric electrons (energies of a few keV to a few tens of keV) through wave-particle interactions, thereby depositing most of their energy at altitudes ~ 100 km. However, the maximum energy of precipitated electrons and its impacts on the atmosphere are unknown. Herein, we report unique observations by the European Incoherent Scatter (EISCAT) radar showing electron precipitations ranging from a few hundred keV to a few MeV during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 41 publications
1
52
0
1
Order By: Relevance
“…By contrast, the B/G ratio distribution in Event 2 did not exhibit a similar characteristic. This tendency may be explained by the precipitation of high-energy electrons from the radiation belt, as reported by Miyoshi, Oyama, et al (2015) and Miyoshi et al (2020Miyoshi et al ( , 2021. As shown in the banana plots of Figures 3 and 4, the aurora oval was located   2 MLAT equatorward in Event 1 as compared with that in Event 2.…”
Section: Spatial Distribution Of B/g Ratiosupporting
confidence: 54%
“…By contrast, the B/G ratio distribution in Event 2 did not exhibit a similar characteristic. This tendency may be explained by the precipitation of high-energy electrons from the radiation belt, as reported by Miyoshi, Oyama, et al (2015) and Miyoshi et al (2020Miyoshi et al ( , 2021. As shown in the banana plots of Figures 3 and 4, the aurora oval was located   2 MLAT equatorward in Event 1 as compared with that in Event 2.…”
Section: Spatial Distribution Of B/g Ratiosupporting
confidence: 54%
“…However, no microburst precipitation was observed during their conjunction, notably when the SAMPEX footprint passed through pulsating aurora. A more recent study by Miyoshi et al (2021) reported an association between pulsating aurora and atmospheric ionization to altitudes as low as 65 km, likely caused by MeV electrons. The handful of studies showing correlation between the pulsating aurora and 1 MeV electrons suggest that the conditions to scatter MeV electrons are more stringent than the conditions to scatter keV electrons, and thus are harder to find (Lee et al, 2012;Summers, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Chen, Gao, Lu, Tsurutani, & Wang, 2021) and within large-scale plasmasphere plumes (Woodroffe et al, 2017;Li et al, 2019;Demekhov et al, 2017Demekhov et al, , 2020, but also near smaller scale structures (Hanzelka & Santolík, 2019;Streltsov & Bengtson, 2020;Hosseini et al, 2021;Ke et al, 2021) which can be formed by compressional ultra-low-frequency waves or localized ionospheric outflows . Ducted chorus waves surviving with large amplitude and low obliquity at middle latitudes (off the equator), can potentially provide effective scattering of relativistic electrons as evidenced by modeling (L. Chen et al, 2020;Miyoshi et al, 2020Miyoshi et al, , 2021. To prove that this type of relativistic electron scattering and precipitation by whistlers actually occurs, it is not sufficient to observe the waves and relativistic electrons at the equator: it also requires confirmation that the waves are ducted, as evidenced by ground-based wave receivers (Manninen et al, 2013;Martinez-Calderon et al, 2015;Shiokawa et al, 2017), and that the relativistic electrons are precipitating, as measured at the ionosphere above the ground station.…”
Section: Accepted Articlementioning
confidence: 99%